2008
DOI: 10.1029/2006jg000319
|View full text |Cite
|
Sign up to set email alerts
|

Application of pulsed‐excitation fluorescence imager for daylight detection of sparse life in tests in the Atacama Desert

Abstract: [1] A daylight fluorescence imager was deployed on an autonomous rover, Zoë, to detect life on the surface and shallow subsurface in regions of the Atacama Desert in Chile during field tests between 2003 and 2005. In situ fluorescent measurements were acquired from naturally fluorescing biomolecules such as chlorophyll and from specific fluorescent probes sprayed on the samples, targeting each of the four biological macromolecule classes: DNA, protein, lipid, and carbohydrate. RGB context images were also acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Other prior applications of fluorescence techniques include assessing the presence of organic compounds or pollutants in the environment [1618], identifying potentially pathogenic or toxic microorganisms in environmental water or food preparation [1922], and detecting trace concentrations of microorganisms in glacial [23] and Antarctic ice [24], Antarctic sandstone [25], and the Atacama desert [26]. …”
Section: Introductionmentioning
confidence: 99%
“…Other prior applications of fluorescence techniques include assessing the presence of organic compounds or pollutants in the environment [1618], identifying potentially pathogenic or toxic microorganisms in environmental water or food preparation [1922], and detecting trace concentrations of microorganisms in glacial [23] and Antarctic ice [24], Antarctic sandstone [25], and the Atacama desert [26]. …”
Section: Introductionmentioning
confidence: 99%
“…Gramain et al (2011) described the archaeal community, identified via nested PCR and cultivation, that occupied a pure halite core up to 15 m deep from the Salar Grande. However, most of the microbiological and life-detection studies on the Atacama Desert have focused mainly on the surface or very close to it (Navarro-González et al, 2003;Lester et al, 2007;Weinstein et al, 2008). Cabrol et al (2007) used a fluorescence detection system on board a rover (Zoë) to detect fluorescent signals from biological material (e.g., chlorophyll) along different transects.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the science team used orbital imagery from ASTER [ Abrams , 2000], Hyperion [ Pearlman et al , 2001], and IKONOS [ Dial et al , 2003] as an integral part of planning over‐the‐horizon traverses. Details about science instrument payload are given by Cabrol et al [2007] and Weinstein et al [2007].…”
Section: Robotic Investigationmentioning
confidence: 99%